The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/medicina58070965
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Pneumothorax Outcome in Preterm and Term Newborns

Abstract: Background and Objectives: Pneumothorax implies the presence of air in the pleural space between the visceral and parietal pleura. The aim of this study was to investigate the incidence, clinical characteristics, risk factors, therapy and perinatal outcome in neonates with pneumothorax in a tertiary care center. Materials and Methods: A retrospective study based on a five-year data sample of neonates with pneumothorax was conducted in a Maternity Hospital with a tertiary NICU from 2015 to 2020. We included all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Although the risk of developing NP is high in premature infants who need resuscitation or who are exposed to IMV due to underlying respiratory problems, the incidence of primary NP in premature infants is also high. 9 , 16 In newborn infants, prematurity and RDS are the most common possible risk factors for NP. 5 According to the study conducted by Joshi et al, 7 50.1% of their study population consisted of preterm infants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the risk of developing NP is high in premature infants who need resuscitation or who are exposed to IMV due to underlying respiratory problems, the incidence of primary NP in premature infants is also high. 9 , 16 In newborn infants, prematurity and RDS are the most common possible risk factors for NP. 5 According to the study conducted by Joshi et al, 7 50.1% of their study population consisted of preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“… 5 - 7 On the other hand, secondary pneumothorax is defined as the pneumothorax that occurs due to traumatic injury to the pleura or risk factors such as meconium aspiration syndrome (MAS), respiratory distress syndrome (RDS), congenital pneumonia, transient tachypnea of the newborn (TTN), surfactant treatment, endotracheal suctioning, pulmonary hypoplasia, or congenital lung malformations, and the use of positive pressure ventilation (PPV) during resuscitation. 7 - 9 Respiratory distress syndrome was found to be the most common possible underlying lung disease of NP for preterm infants and TTN for term infants. 3 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Male gender and cesarian delivery were identified as risk factors for pneumothorax development in most studies, which was confirmed in our study. 3,5,[27][28][29][30][31][32][33][34] Studies report that 51 to 77% of pneumothorax involve the right lung 3,5,31,32,34 and 11 to 24% are bilateral. 5,[30][31][32][33] Consistent with these studies, 65% of our patients had a right pneumothorax, and 25% had a bilateral pneumothorax.…”
Section: Discussionmentioning
confidence: 99%